Planificación estratégica para el desarrollo y gestión de un ecommerce de productos de conveniencia - Cacho Meza, Luis Ricardo (2022)
The objective of this business plan is to create and formalize an e-commerce of convenience products (defined as those that are acquired by the consumer immediately and with minimal effort) that will allow the shopper to make their purchases efficiently and also find a wide range of products on the same platform; thus having a space to make your purchase as complete as possible. Terrazabar is a venture where customers can interact within a personalized digital platform acquiring newer products and higher rotation; as well as guarantee payment security, controlled by a certified payment gateway that ensures a real purchase without danger. The present study contemplates an internal and external analysis of the company with the objective of designing and implementing a strategic plan that allows facing the main problems, dealing with changes in the environment and knowing the opportunities and threats it faces.